Seamilk: innovation of Terminalia Catappa L. seeds as an alternative raw material for plant-based “milk” - Fransiska, Adelia; Septiana, Amanda Rivana; Nugroho, Farenisa Putri; Noerjannah, Diana Laila; Rindy, Aprilliani; Jannah, Nur Bulan (2025)
SeaMilk is an innovative plant-based drink based on ketapang seeds (Terminalia catappa L.), a tropical plant that is abundant in Indonesia but has not been optimally utilised in the food industry. This study explores the potential of ketapang seeds as an alternative raw material for plant-based milk that is nutritious, sustainable, and relevant to a modern healthy lifestyle. The methods used include literature studies, problem identification, and laboratory tests on ketapang seed extract from Yogyakarta using titration and Atomic Absorption Spectroscopy (AAS) methods. The results showed a calcium content of 150 mg/100 mL, magnesium 50 mg/100 mL, and potassium 200 mg/100 mL, with an acidity level of 0.5%, which is safe for consumption. Sensory evaluation revealed that the taste and aroma were acceptable to panellists, comparable to those of soy or almond milk. The flavonoid and tannin content provides bioactive benefits such as antioxidants, anti-inflammatories, and regulation of glucose metabolism. SeaMilk is not only safe for individuals with lactose intolerance but also has the potential to support national nutrition programmes, including preventing stunting through free nutritious meal programmes. This product opens economic opportunities through empowering ketapang farmers and strengthening village food micro, small, and medium enterprises (MSMEs), therefore encouraging food security, as well as inclusive and sustainable local economic development.